The Impact of Deregulation and Liberalization in the Nigerian Air Transport Industry: An Overview - Oluwakoya, Adeniyi (Journal of Air Transport Studies, 2011)
The effect of globalization is fast showing its attendant effects on the Nigerian aviation industry leading to an increase in passengers’ traffic movement in Nigeria’s airports. More importantly, there seems to be a paradigm shift which affects ownership and administration of operation in the Nigerian aviation industry. This study examines among others the impact of deregulation and liberalization in the Nigerian air transport industry; the effects of the latter on operation and control changes that affect operational efficiency in the airline business; and the impacts of liberalization on attracting foreign direct investment and foreign airline participation in the Nigerian aviation industry. The methodology used for this study is documentary research, which entails search of existing published and unpublished documents and databases of stakeholders in the Nigerian aviation industry and external sources with affinity to the sector. The results of this study reveal that an unprecedented growth has been recorded in Nigeria. It includes among others: healthy competition needed for growth and development; increased participation in the industry by foreign airlines; increased foreign direct investment in the airline business and airport infrastructure development.
Keywords: Deregulation; Globalization; Economic Growth; Infrastructure; Nigerian Air Transport; Foreign Direct Investment